Investigation of Sodium Doped Lanthanum Manganite in Optical, Dielectric and Capacitive Perspective Prepared by Flux Method - Majumder, R.; Sarker, M. A. R.; Hossain, M. M.; Hossain, M. E.; Shen, D.; Reza, A. K. M. S.; Kabir, M. H. (Journal of Scientific Research, 2019)
A comprehensive analysis of optical and dielectric properties of a material is very much essential for the research of device fabrication. From this perception, the sodium (Na) doped lanthanum manganite with 15% substitution of La by Na (La0.85Na0.15MnO3) has been synthesized using the flux method and investigated to observe the optical absorbance, refractive index, capacitance and dielectric constant. In this study, we have reported better optical absorbance for the monovalent Na doping with a slightly lower value of the energy band gap ( 1.57 eV) compared to the divalent Sr doping on parent LaMnO3. The structural analysis has been accomplished using X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) to confirm the ability of the flux method to grow higher order La0.85Na0.15MnO3 crystal satisfactorily. Optical properties of La0.85Na0.15MnO3 have been estimated using UV-Vis spectroscopy and the frequency dependent electronic properties (ac conductivity, dielectric constants and capacitance) have been investigated using a precision impedance analyzer. The capacitance has been reported in Pico farad range for La0.85Na0.15MnO3 crystal with the low value of dielectric constant throughout the high-frequency region.